How do dinosaurs stay friends? - Yolen, Jane.; Teague, Mark (New York : The Blue Sky Press, 2016)
A young dinosaur shows how to stay friends even after having a terrible fight with his very best friend.
School Library Journal, January 2016.
Kirkus Review, December 2015.
3.2
K-3
AD470L
Keywords: Dinosaurs -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Dinosaurs -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Dinosaurs -- Fiction; Stories in rhyme; Best friends -- Fiction; Stories in rhyme